ANALISIS PENGARUH PDRB DAN SUKU BUNGA TERHADAP JUMLAH TABUNGAN MASYARAKAT PADA BANK-BANK UMUM DI KALIMANTAN BARAT - B01107037, MITA RISNIMAWATI (Jurnal Pembangunan dan Pemerataan, 2013)
This study entitled "Analysis of Effect of PDRB and Interest Rate to Total Savings Community In Common Banks in West Kalimantan". The purpose of this study was to determine the effect of PDRB Percapita (X1) and interest rates (X2) on the amount of savings in commercial banks in West Kalimantan. The research method used in this research is descriptive quantitative analysis method, a method that describes the influence of the variables examined in accordance with the analytical tools that are used, in order to obtain the facts to get a conclusion. By using secondary data time series is arranged according to the value of the variable time from Bank Indonesia and BPS Office of Pontianak period from 2005 to 2010 and other sources that support this research. Based on the discussions that have been done if the regression results indicate that the PDRB percapita for 0.690 is a positive relationship to the number of private savings while interest rates showed a negative correlation to the amount of -122,269 savings. by R can be seen up and down the amount of variation in the savings banks in West Kalimantan influenced by PDRB percapita and the level of interest rates by 98% while the rest is influenced by other factors in the amount of 2%. It can be concluded that the rise and fall of the amount of savings that people depend on PDRB percapita and the level of interest rates. Keywords: PDRB percapita, Interest Rate, Saving Communities